Short- and long-term outcomes of endoscopic submucosal dissection for undifferentiated early gastric cancer - Abe, Seiichiro; Oda, Ichiro; Suzuki, Haruhisa; Nonaka, Satoru; Yoshinaga, Shigetaka; Odagaki, Tomoyuki; Taniguchi, Hirokazu; Kushima, Ryoji; Saito, Yutaka (Endoscopy, 2013)
Background and study aims: Intramucosal undifferentiated early gastric cancer (EGC) up to 2 cm in size without ulceration has been treated by endoscopic submucosal dissection (ESD) because the incidence of lymph node metastasis is negligible. The aim of this retrospective study was to clarify the short-term and long-term outcomes of ESD carried out to treat undifferentiated EGC.Patients and methods: Between January 1999 and September 2011, 113 patients with poorly differentiated adenocarcinoma or signet ring cell carcinoma on preoperative biopsy underwent ESD. In 16 patients differentiated EGC had been diagnosed after the ESD and these patients were excluded from the study. Short-term outcomes were evaluated in the remaining 97 patients with undifferentiated EGC, and long-term outcomes analyzed in the 79 patients with undifferentiated EGC who had undergone ESD between 1999 and 2008.Results: En bloc and R0 resection were achieved in 99.0 % and 90.7 % of patients, respectively. Median procedure time was 45 minutes. Postoperative bleeding, perforation during the procedure, and delayed perforation were noted in 4.1 %, 3.1 %, and 1.0 % respectively. Curative resection was achieved in 63.9 %. Additional surgery was performed in 21 of 35 patients in whom resection was noncurative: one (4.8 %) had local residual tumor and two (9.5 %) had lymph node metastases. Of the 46 /79 patients in the long-term outcome group who had curative resection, none had local recurrence or lymph node or distant metastasis during a median follow-up of 76.4 months. The 5-year overall mortality rate after curative resection was 7.0 %, and no patient died of gastric cancer.Conclusions: ESD for undifferentiated EGC can achieve curative resection with an excellent 5-year mortality rate.